Experimental standard molar enthalpies of formation of some 4-alkoxybenzoic acids - da Silva, MAVR (2010)
The present work is part of a research program on the energetics of the linear 4-n-alkoxybenzoic acids, aiming the study of the enthalpic effect of the introduction of an alkoxy chain in the position 4- of the benzoic acid ring. In this work, we present the results of the thermochemical research on 4-n-alkoxybenzoic acids with the alkoxy chain length n = 2, 4, and 8. The standard (p degrees = 0.1 MPa) molar enthalpy of formation of crystalline 4-ethoxybenzoic acid, 4-butoxybenzoic acid, and 4-(octyloxy)benzoic acid was measured, at T = 298.15 K, by static-bomb calorimetry. These values, combined with the values of standard molar enthalpies of sublimation, were used to derive the standard molar enthalpies of formation in the gaseous phase. [GRAPHICS] From those experimental values, the standard molar enthalpies of formation, in the gaseous phase, at T = 298.15 K, are interpreted in terms of structural contributions to the energetics of the substituted benzoic acids and compared with the same parameters estimated from the Benson's Group Method.